2004
DOI: 10.1111/j.1601-5223.1998.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Revised Karyotype of Alouatta Caraya (Primates: Platyrrhini) Based on Synaptonemal Complex and Banding Analyses

Abstract: Most primates studied have the usual XXjXY sex-chromosome system. However, exceptions to this rule among howler monkeys have been suggested by several authors. Recently a quadrivalent was discovered in male meiosis of Alouuttu curuyu and it was established that this species has an X,X,Y,Y, sex chromosome system. On that basis, a cytogenetic analysis of 25 males of this species is described, showing the corrected karyotype of this species. Each chromosome involved in the particular sex-chromosome system of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 30 publications
(29 reference statements)
1
36
0
4
Order By: Relevance
“…Regarding the sexual determination, at least two different systems previously characterized by meiotic studies were confirmed: the human-like XX/XY of Cebus paraguayanus (Mantecón et al, 1984) , C. nigritus (Mudry, 1990) , Ateles chamek (Kunkel et al, 1980) and Saimiri boliviensis (García et al, 1995), and the complex sexual system giving a tetravalent X 1 X 1 X 2 X 2 /X 1 X 2 Y 1 Y 2 in Alouatta caraya (Mudry et al, 1998). Other studies proposed a pentavalent and a trivalent in Alouatta guariba clamitans (de Oliveira et al, 2002) and Aotus azarae (Ma et al, 1976), analyzing only mitotic cells.…”
Section: Resultsmentioning
confidence: 76%
“…Regarding the sexual determination, at least two different systems previously characterized by meiotic studies were confirmed: the human-like XX/XY of Cebus paraguayanus (Mantecón et al, 1984) , C. nigritus (Mudry, 1990) , Ateles chamek (Kunkel et al, 1980) and Saimiri boliviensis (García et al, 1995), and the complex sexual system giving a tetravalent X 1 X 1 X 2 X 2 /X 1 X 2 Y 1 Y 2 in Alouatta caraya (Mudry et al, 1998). Other studies proposed a pentavalent and a trivalent in Alouatta guariba clamitans (de Oliveira et al, 2002) and Aotus azarae (Ma et al, 1976), analyzing only mitotic cells.…”
Section: Resultsmentioning
confidence: 76%
“…palliata : Torres and Ramírez, 2003). Multiple sex determination systems have only been confirmed through meiotic analysis for a small number of howler monkey species: trivalents X 1 X 2 Y/X 1 X 1 X 2 X 2 for A. belzebul (Armada et al, 1987) and A. palliata (Solari and Rahn, 2005), and quadrivalents X 1 X 2 Y 1 Y 2 /X 1 X 1 X 2 X 2 for A. seniculus (Lima and Seuánez, 1991) and A. caraya (Rahn et al, 1996;Mudry et al, 1998Mudry et al, , 2001. Fluorescent in situ hybridization (FISH) analyses using human chromosome probes have revealed that the chromosomes involved in the sex chromosome systems hybridize with segments of human chromosomes #3 and #15 (Consigliere et al, 1996(Consigliere et al, , 1998Mudry et al, 2001;de Oliveira et al, 2002).…”
Section: ; Dementioning
confidence: 99%
“…for A. guariba (= fusca) ; Mudry et al, 1998Mudry et al, , 2001Ma et al, 1975 for A. palliata ). An interesting feature in this genus is the presence of several sex chromosome systems among the recognized species.…”
Section: ; Dementioning
confidence: 99%
“…The classical cytogenetic studies allowed researchers to highlight in this genus a large variation in the diploid number, from 2n = 44 to 2n = 58, and two unusual features: a system of multiple sex chromosomes involving a translocation between Y chromosomes and an autosome Armada et al 1987;Mudry et al 1998Mudry et al , 2001Steinberg et al 2008), and the presence of various microchromosomes (Lima & Seuánez 1991), probably composed of repetitive DNA. In the Alouatta genus, Alouatta sara and A. seniculus arctoidea were the first New World monkey species to be analyzed through chromosome painting (Consigliere et al 1996).…”
Section: Atelidae Familymentioning
confidence: 99%